Risk assessment of campylobacteriosis due to consumption of roast beef served in beer bars in Arusha, Tanzania - Makita, K.; Mahundi, E.; Toyomaki, H.; Ishihara, K.; Sanka, P.; Kaaya, E.J.; Grace, Delia; Kurwijila, Lusato R. (Japan Society of Veterinary Epidemiology, 2017)
The objective of the study was to assess the risk of campylobacteriosis due to consumption of cross-contaminated nyama-choma (roast beef) sold in beer bars in Arusha Municipality, Tanzania. In 2010, thirty butchers and thirty beer bars serving roast beef, selected using stratified random sampling, were visited to estimate the prevalence and the most probable number (MPN) of thermophilic Campylobacter in raw and roast beef. Ten purposively selected bars serving roast chicken were also surveyed, to assess cross-contamination after cooking, as Campylobacter spp. are generally more prevalent in poultry. One meat sample was collected in each butcher and each bar, and sales and hygiene were assessed through questionnaires and direct observation. A risk model was developed in statistical software R, and Monte Carlo simulation was performed to estimate disease incidence among customers and the adult male population in Arusha. In the field survey, Campylobacter coli was recovered only from one chicken sample, of which bacterial concentration was 0.37 MPN/g (95% CI : 0.12-1.08). The daily incidence of campylobacteriosis among customers in Arusha was estimated to be 0.15 (95% CI : 0.02-0.95). Annual incidence rates among customers and in the adult male population in Arusha were 12.4 (95% CI : 1.2-83.6) per 1,000 and 0.6 (95% CI : 0.06-4.0) per 1,000, respectively. The most influential factor was the prevalence of thermophilic Campylobacter in roast beef, followed by MPN. Most (26/40, 65%) bar owners sold meat from different species of animals, and cross-contamination could easily occur between poultry and beef. Nearly half (18/39, 46%) the bar owners used the same knife for raw and roast meat. Although half (20/40, 50%) had received hygiene training there was no statistical association between training and separate use of knives for raw and roast meats, considered to be the major source of contamination (x2＝0.22, df＝1, p＝0.64). The study concluded campylobacteriosis from roast beef was a low public health issue in Arusha. However, considering the risks from other types of bacteria, improvement of cooking hygiene training was recommended to further reduce the risk of food-borne diseases from food consumed in beer bars.